Bridging Financial Inclusion through Sharia Fintech: Analyzing Product Innovation in Non-Bank Sharia Institutions - Nisrina Syfa Syaugiah; Supriyanti; Rifqi Rifqi (Lentera Peradaban: Journal on Islamic Studies, 2026)
This study aims to identify and analyze product innovation in Sharia Non-Bank Financial Institutions (SNBFIs) in Indonesia, focusing on driving factors, regulatory challenges, and their implications for institutional performance and sustainability. This research employs a qualitative approach using a library research design with content analysis techniques applied to various literary sources, including scientific journals, books, financial authority reports, and fatwas from the National Sharia Council-MUI. The findings indicate that product innovation in SNBFIs is driven by increasingly diverse customer needs, advancements in digital technology, and industrial competitive pressures. A prominent form of innovation is the development of Sharia fintech-based financing services, such as Sharia peer-to-peer lending and crowdfunding, which enable faster and more inclusive access to MSME financing. However, these innovations face various challenges, particularly regarding stringent Sharia regulations that require fatwa validation processes, a shortage of human resources with dual competencies (both in fiqh muamalah and technology), and limited funding for research and development. The implications of this study affirm that product innovation serves not only as a strategy to enhance competitiveness but also as an instrument to expand financial inclusion and strengthen the Sharia economic ecosystem. Therefore, adaptive policy support is required, such as the development of more flexible regulatory sandboxes, to foster innovations that remain aligned with Sharia principles and the objectives of maqasid al-sharia, specifically the attainment of collective welfare (falah).